A phenomenological study of Christian practitioners who use mindfulness. Issue 3 (3rd July 2018) - Trammel, Regina Chow
ABSTRACT: Mindfulness is the practice of present-moment awareness with nonjudgment. Mindfulness-based therapies draw from secular or Buddhist frameworks. Including other religious traditions that also incorporate mindfulness assists in skill attainment. This descriptive phenomenological study explores the lived experience of nine Christian mental health practitioners. Three themes resulted: a divine presence in session guides and affirms practitioners' work; practitioners' increased attunement to clients in clinical work; and integration of the sacred and the secular in treatment. Practitioners using mindfulness with clients strengthened their ability to be aware of spiritual aspects of themselves suggesting implications for training mental health practitioners to enhance therapeutic praxis.